Scaling Down Characteristics of Vertical Channel Phase Change Random Access Memory (VPCRAM) - Park, Chun Woong; Park, Chongdae; Choi, Woo Young; Seo, Dongsun; Jeong, Cherlhyun; Cho, Il Hwan (IEEK PUBLICATION CENTER, 2014)
In this paper, scaling down characteristics of vertical channel phase random access memory are investigated with device simulator and finite element analysis simulator. Electrical properties of select transistor are obtained by device simulator and those of phase change material are obtained by finite element analysis simulator. From the fusion of both data, scaling properties of vertical channel phase change random access memory (VPCRAM) are considered with ITRS roadmap. Simulation of set reset current are carried out to analyze the feasibility of scaling down and compared with values in ITRS roadmap. Simulation results show that width and length ratio of the phase change material (PCM) is key parameter of scaling down in VPCRAM. Thermal simulation results provide the design guideline of VPCRAM. Optimization of phase change material in VPCRAM can be achieved by oxide sidewall process optimization.